An Approach to Macroscopic Central Lymph Nodes Detected during Surgery in Patients with Thyroid Micropapillary Carcinoma: Should We Resort to Dissection? - Osman Kurukahvecioglu; Kursat Dikmen; Hasan Bostanci; Murat Akin; Ferit Taneri (International Journal of Endocrinology)
Background. High-resolution ultrasonography and the ability to perform fine-needle aspiration biopsy even for nodules smaller than three millimeters have considerably increased the detection rate of thyroid micropapillary carcinoma (TMPC). Despite favorable prognosis, the prevalence of cervical lymph node metastases in patients with TMPC is approximately 30%. Aim. In this study, we aimed to determine the central lymph node metastasis rate and its relation to the characteristics of the tumor. Methods. One hundred nine patients who underwent surgery due to TMPC between December 2009 and January 2014 were analyzed retrospectively. Patients were divided into two groups according to whether they underwent lymph node dissection and the two groups were then compared with respect to tumor size and multicentricity, age, and presence of lymphocytic thyroiditis. Results. There were no statistically significant differences between the two groups of patients in terms of tumor size, tumor multicentricity, age, and presence of lymphocytic thyroiditis. When the patient group that received lymph node dissection was further analyzed, it was found that patients with lymphocytic thyroiditis had a significantly lower number of metastatic lymph nodes. Conclusion. Central lymph node dissection in TMPC patients with macroscopic lymph node detected intraoperatively would ensure accurate staging without an increase in morbidity.